Factors Affecting Environmental Disclosure in Companies Listed on the Tokyo Stock Exchange - Istiqomah, Istiqomah; Wahyuningrum, Indah Fajarini Sri (Universitas Negeri Semarang, 2020)
This study aims to examine the factors influence environmental disclosure such as company financial performance, company characteristics, corporate governance mechanism, and environmental management system. Environmental disclosure in this study used the content analysis method by calculating the number of sentences for each disclosure item based on GRI Standards 2016. The population of this study are 1st section companies listed in Tokyo Stock Exchange (TSE) during the period of 2016 to 2017 which consist of 2.062 companies. Sampling in this study used a purposive sampling technique. There are 47 companies as the research sample and 94 firms-year observations. This study used multiple linear regression analysis to determine the effect of independent variables on environmental disclosure. The result of the statistic analysis is firm size and firm age have a positive significant effect on environmental disclosure. ROE, corporate governance mechanism, and EMS have no significant effect on environmental disclosure, while NPM has a negative significant effect. The conclusion of this study is the environmental disclosure quantity positively influenced by firm age and firm size. The bigger and older companies proved disclose better environmental information by writing more narration or explanation of each environmental disc